Magnetic Resistance And Mobility Of Carriers Of HTSC - YBCO Tapes Irradiated With 5 Mev Electrons (Eurasian Journal of Physics,Chemistry and Mathematics, 2024)
Structural defects were studied in metal-coated microfilms of high-temperature superconductor YBa2Cu3O7-x on steel tape SuperOx-1, which were created by irradiation in air at 273 K with 5 MeV electron beam at a current of 400 nA to a fluency of 5x1014 e/cm2. Magnetoresistance peaks within 100–300 K decreased by a factor of 10 after the irradiation, a correlated increase in resistivity by >103 times and a decrease in carrier mobility by >103 times were found at 120–160 K and 230 K. This indicates the formation of magnetic flux pinning centers, phase transitions of the 2nd order from a normal metal to a mixed magnetic vortex state, and then to the superconducting state. After the irradiation the fractions of Cu and Y2O3 crystal phases decreased due to generation of displacement defects of Cu and O atoms, and radiation-stimulated crystallization of the YBa2Cu2O7 superconducting phase occurred simultaneously